2020
DOI: 10.3389/fimmu.2019.02980
|View full text |Cite
|
Sign up to set email alerts
|

Amyloids in Site-Specific Autoimmune Reactions and Inflammatory Responses

Abstract: Amyloid deposition is a histological hallmark of common human disorders including Alzheimer's disease (AD) and type 2 diabetes. Although some reports highlight that amyloid fibrils might activate the innate immunity system via pattern recognition receptors, here, we provide multiple lines of evidence for the protection by site-specific amyloid protein analogs and fibrils against autoimmune attacks: (1) strategies targeting clearance of the AD-related brain amyloid plaque induce high risk of deadly autoimmune d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 202 publications
0
2
0
Order By: Relevance
“…Although incidence of myocardial inflammation in cardiac amyloidosis is unknown, in our referral center, which handles many endomyocardial biopsies (EMBs) and numerous whole transplanted hearts of patients with amyloidosis, we had the opportunity to study myocardial inflammatory infiltrates associated to amyloid deposits, varying from simply lymphocytic or macrophagic-lymphocytic to giant cell granulomatous inflammation (Figure 5). Data are still scanty, but literature documented that amyloid may play a role in immune/autoimmune response (38). The issue of amyloidosis and inflammation is yet based on isolated and preliminary observations and research is needed to expand knowledge on pathogenetic mechanisms, possible role of inflammatory infiltrates on deposits, interactions with specific amyloidosis type and impact on disease progression and survival or on future therapeutic implication (39)(40)(41).…”
Section: Focus On the Heartmentioning
confidence: 99%
“…Although incidence of myocardial inflammation in cardiac amyloidosis is unknown, in our referral center, which handles many endomyocardial biopsies (EMBs) and numerous whole transplanted hearts of patients with amyloidosis, we had the opportunity to study myocardial inflammatory infiltrates associated to amyloid deposits, varying from simply lymphocytic or macrophagic-lymphocytic to giant cell granulomatous inflammation (Figure 5). Data are still scanty, but literature documented that amyloid may play a role in immune/autoimmune response (38). The issue of amyloidosis and inflammation is yet based on isolated and preliminary observations and research is needed to expand knowledge on pathogenetic mechanisms, possible role of inflammatory infiltrates on deposits, interactions with specific amyloidosis type and impact on disease progression and survival or on future therapeutic implication (39)(40)(41).…”
Section: Focus On the Heartmentioning
confidence: 99%
“…It has also been reported that oxidative stress causes increased Aβ deposition and formation of aggregates in neuronal cells, which is recognized as a hallmark of AD. The differential analysis of Aβ peptides and amyloids proteins in RA will be an effective method that offers protection from an autoimmune response and cartilage destruction to inflammation [88].…”
Section: Non-ages Ligands and Inflammationmentioning
confidence: 99%